Attitudes about and correlates of cannabis legalization policy among U.S. young adults. Issue 8 (17th November 2021) - Rudy, Alyssa K.; Barnes, Andrew J.; Cobb, Caroline O.; Nicksic, Nicole E.
Abstract: Objective: Cannabis policies are rapidly evolving in the US. This study's purpose was to examine relationships between cannabis harm perceptions, substance use, and demographic characteristics on attitudes toward cannabis policies. Participants: Participants were 619 undergraduate students in a Mid-Atlantic state where cannabis use was illegal. Methods: In 2016, participants completed a cross-sectional survey. Multinomial logistic regressions tested associations between attitudes toward cannabis policies (recreational cannabis use, use in private, or public) while controlling for harm perceptions, substance use, and demographics. Results: The majority (64%) of participants supported recreational cannabis legalization, while 78% supported private and 29% supported public use. Perceiving cannabis as less harmful and current cannabis use were positively associated with supporting all three cannabis policies. Conclusions: Results highlight diversity of young adults' opinions regarding specific cannabis policies and underscore relationships between cannabis use behaviors, harm perceptions, and support for legalization that may inform policy making and prevention efforts.